2020
DOI: 10.3389/feduc.2020.00104
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Reliable Predictors of Educational Outcomes Through Machine-Learning Predictive Modeling

Abstract: Results-based financing has guided the development of policies with measurable results improving learning outcomes at micro/macro levels. However, it is then necessary to identify factors which predict early and accurately favorable or challenging conditions for learning. Learning outcomes depend on complex interactions between multiple variables, many of which are not fully understood. The objective was to develop valid and accurate models predicting low and high levels of math performance and Vietnamese lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Some authors have shown that traditional statistical methods do not always yield accurate predictions and/or classifications (Bansal, Kauffman, & Weitz, 1993; Duliba, 1991; Everson, 1995). A more robust and accurate approach has been developed during the last decade and applied in health and education fields for the purpose of prediction (Cascallar, Boekaerts, & Costigan, 2006; Everson, Chance, & Lykins, 1994; Gorr, 1994; Hardgrave, Wilson, & Walstrom, 1994; Musso & Cascallar, 2009; Musso et al, 2012; Musso, Kyndt, Cascallar, & Dochy, 2013; Musso, Cascallar, Bostani, & Crawford, 2020; Musso, Hernández, & Cascallar, 2020). Machine‐learning techniques, such as methods using artificial neural networks (ANN), have been shown to be very effective to study problems consisting of a large number of variables in complex, nonlinear, and poorly understood interactions (Cascallar, Musso, Kyndt, & Dochy, 2014).…”
mentioning
confidence: 99%
“…Some authors have shown that traditional statistical methods do not always yield accurate predictions and/or classifications (Bansal, Kauffman, & Weitz, 1993; Duliba, 1991; Everson, 1995). A more robust and accurate approach has been developed during the last decade and applied in health and education fields for the purpose of prediction (Cascallar, Boekaerts, & Costigan, 2006; Everson, Chance, & Lykins, 1994; Gorr, 1994; Hardgrave, Wilson, & Walstrom, 1994; Musso & Cascallar, 2009; Musso et al, 2012; Musso, Kyndt, Cascallar, & Dochy, 2013; Musso, Cascallar, Bostani, & Crawford, 2020; Musso, Hernández, & Cascallar, 2020). Machine‐learning techniques, such as methods using artificial neural networks (ANN), have been shown to be very effective to study problems consisting of a large number of variables in complex, nonlinear, and poorly understood interactions (Cascallar, Musso, Kyndt, & Dochy, 2014).…”
mentioning
confidence: 99%
“…Singhal et al [36] proposed a logical structure to improve presentation of a web page, making it more userfriendly to promote e-business. Musso et al [37] used machine learning predictive models to predict low and high levels of performances in subjects in educational systems. Márquez-Chamorro et al [38] summarises about basic concepts of predictive monitoring area in business processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But unfortunately, more often these skilled persons are not that much educated overtime. Due to low level of literacy, they could not match themselves with the fast pace of online business applications and their practice [37]. Hence, they are lagging behind financially.…”
Section: Data Modelmentioning
confidence: 99%
“…Topic Modeling [57] is a rapidly emerging area of research in educational data mining. Text analysis methods in education research have been used to 1) measure latent dispositions such as attitudes and beliefs of learners and instructors [60]; 2) explore the underlying topics and topic evolution spanning the 50-year history of educational leadership research literature [61]; 3) microclassroom processes such as MOOC interaction data [62]; 4) policy implementation and reform strategies [63]; or 5) identifying 'topics' of multiple setting-level predictors of student's language and math achievement outcomes [64]. Despite the promising potential of applying topic modeling in a variety of fields in the social sciences, its scalable, algorithmic approach to large-scale text data has received little attention among early childhood and education policy scholars [61].…”
Section: A Machine Learning Approach To Early Childhood Development Policy Analysismentioning
confidence: 99%
“…However, a burgeoning body of work has applied machine learning algorithms in educational research to better understand how teaching and learning can be enhanced for whom under what conditions [60,89]. Recent studies, for example, have built artificial neural network models that predict students' language and math performance at large scale [64], introduced various methods in educational data science (EDS) for examining students' massive open online courses (MOOCs) interactions [62], or using LDA to analyze text data from thousands of school improvement reports to identify reform mechanisms that reduced student chronic absenteeism and improved achievement [63]. As such text mining can enhance administrative data that many early childhood researchers have been utilizing for decades as well as address barriers and limitations surrounding administrative data by adding richness that is often buried in digital text without the cost of primary data collection.…”
Section: Promise and Limitations Of Big Data In Predicting The Future Of Early Childhood Policymentioning
confidence: 99%